2012
DOI: 10.1371/journal.pbio.1001257
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Complexes Promote Trinucleotide Repeat Expansions

Abstract: Genetic analysis in budding yeast and in cultured human astrocytes reveals that specific histone deacetylase complexes accelerate expansion mutations in DNA triplet repeats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 47 publications
4
102
1
Order By: Relevance
“…1D); therefore this HDAC is not involved in protection against CAG expansions. Interestingly, loss of Rpd3 did lead to a significant decrease in contraction frequency (Table S1), similar to the suppression of (CAG) 20 expansions observed after Rpd3L knockdown, which was attributed to stabilization of the Sae2 nuclease (Debacker et al, 2012). Hda1 also targets both histone H3 and the Sae2 nuclease (Robert et al, 2011), and we showed previously that Sae2 is required to prevent (CAG) 70 expansions (Sundararajan et al, 2010).…”
Section: Resultssupporting
confidence: 61%
“…1D); therefore this HDAC is not involved in protection against CAG expansions. Interestingly, loss of Rpd3 did lead to a significant decrease in contraction frequency (Table S1), similar to the suppression of (CAG) 20 expansions observed after Rpd3L knockdown, which was attributed to stabilization of the Sae2 nuclease (Debacker et al, 2012). Hda1 also targets both histone H3 and the Sae2 nuclease (Robert et al, 2011), and we showed previously that Sae2 is required to prevent (CAG) 70 expansions (Sundararajan et al, 2010).…”
Section: Resultssupporting
confidence: 61%
“…It is important to note that Msh2-Msh3-mediated expansions are just one mechanism by which TNR tracts increase in length. This yeast system is amenable to examining the contribution of additional genetic factors on tract dynamics in both deletion and mutation backgrounds (e.g., Debacker et al 2012;Concannon and Lahue 2014)). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that histone deacetylase complexes promote instability in threshold size (CAG⅐CTG) 20 repeats in budding yeast and human astrocytes. HDAC inhibitors targeting those complexes strongly reduced the propensity of the (CAG⅐ CTG) 20 repeats to expand (70). If this effect translates to the longer GAA⅐TTC repeats in FRDA, then the HDAC inhibitors currently being studied as potential FRDA therapeutics may serve double duty by: 1) increasing transcription through the repeat and 2) suppressing further expansion.…”
Section: Discussionmentioning
confidence: 99%